THE WAYS TO EXPAND THE RANGE OF YEAST-FREE BAKERY PRODUCTS - M. P. Baisbaeva; B. A. Iztaev; M. A. Yakiyaeva; Z. N. Moldakulova; A. K. Izembayeva; G. K. Iskakova (Современная наука и инновации, 2022)
Defined organoleptic and physicochemical parameters quality non-yeasted bakery (physicochemical parameters, organoleptic .) Using the dough intensive technology.